EMPOWERING YOUNG VOICES: ENHANCING SPEAKING SKILLS THROUGH VISUAL AIDS - Annisa Ul Miftahul Jannah Rusdin; Ari Purnawan (Universitas Muhammadiyah Makassar, 2026)
Speaking competence remains a major challenge for junior high school students learning English, as many struggle to express ideas confidently and interact fluently. Addressing this urgent issue, this study investigates the effectiveness of visual aids in enhancing students’ speaking performance. Employing Classroom Action Research (CAR) conducted in two cycles, data were collected through observations, interviews, and pre- and post-tests. The findings reveal a meaningful descriptive impr ovement in students’ speaking scores, rising from 2.94 (pre-test) to 3.45 (Cycle I) and 4.04 (Cycle II), reflecting a gradual improvement of 17.3% in Cycle I and 37.4% in Cycle II compared to the initial condition. Beyond measurable progress, visual aids also increased student motivation and active participation. The novelty of this study lies in integrating contextual and engaging visuals to stimulate communicative interaction. These results highlight the significant contribution of visual-based strategies in fostering meaningful and student-centered English learning, providing practical insights for teachers seeking to enhance speaking instruction through creative classroom media.